2013
DOI: 10.1186/1477-7525-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character properties of primary focal hyperhidrosis patients

Abstract: BackgroundPrimary focal hyperhidrosis is a health problem, which has negative effects on the patient's quality of life and significantly affects the patients’ daily activities, social and business life. The aim of this study is to evaluate temperament and character properties of patients diagnosed with primary focal hyperhidrosis.MethodsFifty-six primary focal hyperhidrosis (22.42 ± 7.80) and 49 control subjects (24.48 ± 5.17) participated in the study. Patients who met the diagnostic criteria for PFH were ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Signs PH may affect a patient’s personality traits and interpersonal relations are found in increased association with alexithymia [22], fatigability and asthenia, self-forgetfulness and self-transcendence, as well as decreased association with purposefulness, resourcefulness, self-directedness. [23]. Prevalence of anxiety and depression among hyperhidrosis patients is nearly triple that of the population, proportional to disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Signs PH may affect a patient’s personality traits and interpersonal relations are found in increased association with alexithymia [22], fatigability and asthenia, self-forgetfulness and self-transcendence, as well as decreased association with purposefulness, resourcefulness, self-directedness. [23]. Prevalence of anxiety and depression among hyperhidrosis patients is nearly triple that of the population, proportional to disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…While emotional stress itself can trigger HH, HH may also cause emotional stress, and thus increase oxidative stress. 37 In a study conducted on the etiology of patients with HH, we detected vit D deficiency in patients and observed decrease in sweating in patients supplemented with vit D. 38 In another study, it was reported that thiol-disulfide balance was affected by vit D deficiency. 39 In this study, vit D deficiency was found in 69.7% of patients with PHH and in 60% of patients with SHH (64.4% in total).…”
Section: Discussionmentioning
confidence: 96%
“…Although some authors concluded that the relationship between sweating pattern and emotional pattern, specific disorders, or family relationship history is absent (Karaca et al, 2007 ; Ruchinskas, 2002 ; Won et al, 1998 ), Ak ( 2013 ) found that individuals with hyperhidrosis were characterized by specific personality traits, temperament, and character features compared to controls, associated to lower purposefulness, resourcefulness, self-directedness and higher self-forgetfulness and self-transcendence. Moreover, Johnson and Mostaghimi ( 1995 ) reported the hyperhidrosis as the most frequent dermatological disorder in psychiatric subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Johnson and Mostaghimi ( 1995 ) reported the hyperhidrosis as the most frequent dermatological disorder in psychiatric subjects. Most importantly, we can note that some studies investigated the possibility of personality traits as an etiological factor for primary hyperhidrosis (Ak, 2013 ), while others either refuted etiological conclusions (Karaca et al, 2007 ; Won et al, 1998 ), or considered the psychological differences to be the result of hyperhidrosis and not its cause (Ruchinskas et al, 2002 ). The idea of this study arose from our thought that the impact of this illness on psychological well-being might depend on the personality functioning.…”
Section: Introductionmentioning
confidence: 99%